A novel features prioritization mechanism for controllers in software-defined networking - Ali, Jehad; Lee, Byungkyu; Oh, Jimyung; Lee, Jungtae; Roh, Byeong Hee (Computers, Materials and Continua, 2021)
The controller in software-defined networking (SDN) acts as strategic point of control for the underlying network. Multiple controllers are available, and every single controller retains a number of features such as the OpenFlow version, clustering, modularity, platform, and partnership support, etc. They are regarded as vital when making a selection among a set of controllers. As such, the selection of the controller becomes a multi-criteria decision making (MCDM) problem with several features. Hence, an increase in this number will increase the computational complexity of the controller selection process. Previously, the selection of controllers based on features has been studied by the researchers. However, the prioritization of features has gotten less attention. Moreover, several features increase the computational complexity of the selection process. In this paper, we propose a mathematical modeling for feature prioritization with analytical network process (ANP) bridge model for SDN controllers. The results indicate that a prioritized features model lead to a reduction in the computational complexity of the selection of SDN controller. In addition, our model generates prioritized features for SDN controllers.
Keywords: Analytical network processes (ANP); Controller selection; Multi-criteria decision making; Multiple controllers; Prioritization mechanism; Single controllers; Software defined networking (SDN); Underlying networks; Analytical hierarchy process; Analytical network process; Controllers; Feature-based selection; Quality-of-service; Software-defined networking